Forensic-Medical Characteristics of Diagnosis Defects (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
According to the materials of the forensic medical service, it was revealed that defects in medical care were more often found in the activities of surgeons and mid-level medical personnel, diagnostic defects predominated in nature (most often failure to recognize the underlying pathology), which mainly arose due to subjective reasons (mainly due to insufficient qualifications of medical personnel), more often at the hospital stage and in the outcome in most cases led to death.